Elements of forecasting - Diebold, Francis X. (Thomson/South-Western, 2007)
Elements of Forecasting is a concise, modern survey of business and economics forecasting methods. Written by a leading expert on forecasting, it focuses on the core techniques of widest applicability and assumes only an elementary background in statistics. It is applications-oriented and illustrates all methods with detailed examples and case studies.